Missed Nursing care as related to ethical climate: a pilot study - Papastavrou, Evridiki; Vryonides, Stavros; Charalambous, Andreas; Merkouris, Anastasios; Sarafis, Pavlos (My University, 2015)
A phenomenon investigated within the framework ofscarcity ofresources, costreductions and economic constraints. •Thedominating view is that when resources arenotsufficient toprovide necessary careto allpatients, nursesareforced to rationtheirattention acrosspatients byusingtheirclinicaljudgmentto prioritiseassessmentsand interventions whichmayincrease the riskofnegativepatientoutcomes(Schubertetal., 2008).
Keywords: Nursing care; Ethical climate